Facile synthesis of Mn-doped NiCo2O4 nanoparticles with enhanced electrochemical performance for a battery-type supercapacitor electrode. Issue 20 (5th May 2020) - Nguyen, To Van; Son, Le The; Thuy, Vu Van; Thao, Vu Dinh; Hatsukano, Masahito; Higashimine, Koichi; Maenosono, Shinya; Chun, Sang-Eun; Thu, Tran Viet
Abstract : We report the synthesis of manganese-doped nickel cobalt oxide (Mn-doped NiCo2 O4 ) nanoparticles (NPs) by an efficient hydrothermal and subsequent calcination route. Abstract : We report the synthesis of manganese-doped nickel cobalt oxide (Mn-doped NiCo2 O4 ) nanoparticles (NPs) by an efficient hydrothermal and subsequent calcination route. The material exhibits a homogeneous distribution of the Mn dopant and a battery-type behavior when tested as a supercapacitor electrode material. Mn-doped NiCo2 O4 NPs show an excellent specific capacity of 417 C g −1 at a scan rate of 10 mV s −1 and 204.3 C g −1 at a current density of 1 A g −1 in a standard three-electrode configuration, ca. 152–466% higher than that of pristine NiCo2 O4 or MnCo2 O4 . In addition, Mn-doped NiCo2 O4 NPs showed an excellent capacitance retention of 99% after 1000 charge–discharge cycles at a current density of 2 A g −1 . The symmetric solid-state supercapacitor device assembled using this material delivered an energy density of 0.87 μW h cm −2 at a power density of 25 μW h cm −2 and 0.39 μW h cm −2 at a high power density of 500 μW h cm −2 . The cost-effective synthesis and high electrochemical performance suggest that Mn-doped NiCo2 O4 is a promising material for supercapacitors.